Life cycle assessment of battery electric buses. (November 2022) - Ager-Wick Ellingsen, Linda; Jayne Thorne, Rebecca; Wind, Julia; Figenbaum, Erik; Romare, Mia; Nordelöf, Anders
Graphical abstract: Abstract: Different Li-ion battery technologies and sizes are used in battery electric buses (BEBs), but little is known about the environmental effect of various battery technology and sizing alternatives. In a cradle-to-grave life cycle assessment of seven BEBs, we consider three battery technologies combined with relevant pack sizes to evaluate the size and range effect. The environmental performance of the BEBs was assessed over the typical length of a bus tender of 10 years as well as an extended lifetime of 20 years. Across six environmental impact categories we found that the size and range effect depends to a large extent on the performance of the battery technology and that a smaller battery size of the same technology is not necessarily environmentally preferable. Furthermore, extending the BEB lifetime from 10 to 20 years changes the environmental performance as well as relative contributions to environmental impact potentials for the various BEB alternatives.